TREATMENT OF CANINE TRANSMISSIBLE VENEREAL TUMOR IN FEMALE LABRADOR RETRIEVER WITH EXCISION AND CHEMOTHERAPY: A CASE REPORT - Ni Komang, Nadia Eprillia Sary Darma; Pemayun, I Gusti Agung Gede Putra (Buletin Veteriner Udayana, 2022)
Canine transmissible venereal tumor (CTVT) or known as infectious sarcoma, is a genital tumor that is transmitted through sexual contact, bites or licks on the tumor lesion area. A 7-year-old Labrador Retriever with 40 kg of body weight was examined with a complaint of a mass on the vulva with blood discharge. Histopathological examination showed the presence of CTVT tumor cells with homogeneous polyhedral cells and arranged in stroma. Treatment is done by excision of the tumor mass. Premedication was given atropine sulfate (0.02 mg/kg) intramuscularly and 15 minutes later was induced by combination xylazine (1 mg/kg) and ketamin (10 mg/kg) intramuscularly.  Postoperatively, the antibiotic amoxicillin (7 mg/kg) was administered intramuscularly and the antibiotic amoxicillin 500 mg (15 mg/kg) was administered on the second postoperative day, given orally three times a day for five days. On the 5th postoperative day, the tumor incision wound had dried up and the swelling of the vulva was much reduced, but there was still blood discharge indicating the presence of venereal cells that were left behind. The first dose of chemotherapy using vincristine sulfate (0.025 mg/kg) was given on the seventh postoperative day with one-week interval. The blood discharge was gone on the 7th day after the first chemo. The conclusion is, the treatment of CTVT cases with excision method accompanied with chemotherapy gives good results on patient’s recovery. It’s recommended to perform hematology and echocardiography test before chemotherapy to ensure the patient is in stable condition.